2010
DOI: 10.1073/pnas.0913800107
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on empirical approaches for ocean color remote sensing of chlorophyll in a changing climate

Abstract: Phytoplankton biomass and productivity have been continuously monitored from ocean color satellites for over a decade. Yet, the most widely used empirical approach for estimating chlorophyll a (Chl) from satellites can be in error by a factor of 5 or more. Such variability is due to differences in absorption and backscattering properties of phytoplankton and related concentrations of colored-dissolved organic matter (CDOM) and minerals. The empirical algorithms have built-in assumptions that follow the basic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(115 citation statements)
references
References 55 publications
2
107
0
2
Order By: Relevance
“…Confidence in the satellite estimates of SeaWiFS TCHLa can be taken from the fact that they compare favourably with weekly and daily AMT match-ups (Aiken et al, 2009;Brewin et al, 2010). Furthermore, seasonal and inter-annual variations (including trends) in SeaWiFS TCHLa are consistent with those derived using the MODISAqua and MERIS ocean-colour sensors over a similar time-period (2002-2010see Brewin et al, 2014c), lending confidence to the SeaWiFS results. Blending in-situ and satellite observations of TCHLa (e.g.…”
Section: Trends In Total Chlorophyll-amentioning
confidence: 54%
See 2 more Smart Citations
“…Confidence in the satellite estimates of SeaWiFS TCHLa can be taken from the fact that they compare favourably with weekly and daily AMT match-ups (Aiken et al, 2009;Brewin et al, 2010). Furthermore, seasonal and inter-annual variations (including trends) in SeaWiFS TCHLa are consistent with those derived using the MODISAqua and MERIS ocean-colour sensors over a similar time-period (2002-2010see Brewin et al, 2014c), lending confidence to the SeaWiFS results. Blending in-situ and satellite observations of TCHLa (e.g.…”
Section: Trends In Total Chlorophyll-amentioning
confidence: 54%
“…For instance, it has been shown that information on the absorption and backscattering properties of phytoplankton size is implicit in remote-sensing algorithms that empirically relate TCHLa to band-ratio reflectance (Dierssen, 2010;IOCCG, 2014). In fact, these algorithms implicitly assume a fixed relationship between PSC and TCHLa (IOCCG, 2014).…”
Section: Implications Of Modifications In the Relationship Between Psmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard chlorophyll a (Chl a) algorithm, however, fails in the optically complex coastal waters of WLIS due to rich concentrations of suspended minerals and colored dissolved organic matter (CDOM) (16)(17)(18). These blue-absorbing and scattering constituents can mimic the water color produced by phytoplankton and result in overestimates of their abundance, as shown by the high Chl a estimates throughout the sound (Fig.…”
Section: Significancementioning
confidence: 99%
“…2A). Tuned to open ocean conditions (16), the limited spectral information prevents differentiation of an M. rubrum bloom from other types of phytoplankton known to occur in this region (e.g., diatoms, dinoflagellates) (17).…”
Section: Significancementioning
confidence: 99%